2016
DOI: 10.1002/cmmi.1703
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging, targeting and characterization of pulmonary fibrosis using intra‐tracheal administration of gadolinium‐based nanoparticles

Abstract: Idiopathic pulmonary fibrosis is a devastating disease. Animal models are critical to develop new diagnostic approaches. We investigate here whether the application of an ultra-short echo time MRI sequence combined with the intra-tracheal administration of Gd-based nanoparticles can help to visualize and characterize pulmonary fibrosis in mice. 21 mice were imaged. Treated mice were administered bleomycin. MRI was used for longitudinal detection of bleomycin-induced lung injury from Day 1 up to Day 60. On Day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Considering the favourable kinetics of these nanoparticles in the lungs (residence time in the order of 1 hour in the lung tissue) followed by an effective and complete renal clearance, several animal models of lung disease were then investigated. For instance, Tassali et al 39 investigated the application of lung MRI protocol combined with the intratracheal administration of the SRP in a bleomycin-induced fibrotic mouse model. The authors reported an MRI signal enhancement of 120% in fibrotic lesions as compared to 50% in healthy tissues and a twofold increase of contrast-to-noise ratio between fibrotic and healthy tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the favourable kinetics of these nanoparticles in the lungs (residence time in the order of 1 hour in the lung tissue) followed by an effective and complete renal clearance, several animal models of lung disease were then investigated. For instance, Tassali et al 39 investigated the application of lung MRI protocol combined with the intratracheal administration of the SRP in a bleomycin-induced fibrotic mouse model. The authors reported an MRI signal enhancement of 120% in fibrotic lesions as compared to 50% in healthy tissues and a twofold increase of contrast-to-noise ratio between fibrotic and healthy tissue.…”
Section: Discussionmentioning
confidence: 99%
“…NLC were developed by nanostructuring the lipid matrix in order to give more flexible control of drug release, increasing the loading efficiency for drugs like PGE2 which possesses poor water solubility, and preventing drug leakage. Among the different approaches to modeling pulmonary fibrosis, bleomycin remains the most frequently used agent and can be given directly into the airway by intratracheal administration 20, 21 . The major advantage of the intratracheal bleomycin model is the short time between the drug instillation and the manifestation of fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results support the growing interest in drug and contrast agent delivery via the airways to target and diagnose several diseases of the lungs, 18,53,54 but also of other organs. 49,55 The bulk of the literature seems to suggest that direct pulmonary administration is an effective, simple and reliable route for lung and systemic delivery of drugs. [56][57][58] Further studies are needed to shed light on this efficient and promising administration route.…”
Section: Discussionmentioning
confidence: 99%